Adventure tourism in Kampar, Malaysia: profile and visit characteristics of domestic visitors - Mohamed, Zulkifli; Mohammad Afandi, Syamsul Herman; Ramachandran, Sridar; Shuib, Ahmad; Kunasekaran, Puvaneswaran (Universiti Malaysia Sarawak, 2018)
There were 7.96 million domestic tourist arrivals to Perak in 2015, which marked an increase of 13.71 percent over the previous year. The arrival of domestic tourists to Perak in general and Kampar in particular have prompted a significant increase in demand for facilities and services for adventure tourism activities in Kampar, which is considered to be one of the icons of tourism in the state of Perak. However, a lack of information on the profile of visitors has hampered industry players in Kampar when it comes to identifying their target markets, marketing strategies, and added value products without losing sight of conservation priorities in Kampar. The aim of this study was to determine the profile and visit characteristics of visitors in Kampar from the perspective of adventure tourism. To achieve this objective, a study was conducted on domestic visitors who participated in the adventure tourism activities available in Kampar. On-site data from 102 visitors were collected. The results showed that adventure tourism in Kampar is comprised of visitors with an average age of 33 years and a mean monthly income of RM 3638.72. Most of them travel with friends and obtained the information about the destination through word of mouth and social media platforms. The findings of the study can be used by stakeholders to understand the characteristics and motivations of adventure tourists in order to plan the best approach for the promotion and marketing of adventure tourism to this segment.